The Highlighting Students’ Voices of Learning English Through Project-Based Learning During Covid-19 Pandemic: A Case Study - Rahmania, Vina Kautsar; Suharjito, Bambang; Hudori, Rizki Febri Andika (Universitas Muhammadiyah Malang, 2023)
All the students need to adapt to the new version of the learning and teaching process. The use of project-based learning in the COVID-19 pandemic can help students who struggle to make an interaction with other students. This approach can help vocational high school students more easily understand the topic by using projects that relate to their workplace. This project aimed to explore the students’ voices using Project-based learning in English learning in the pandemic era. This case study used semi-structured interviews to interview five students from one of the vocational high schools in Jember that had already used the project-based learning method during a pandemic. This research results show that project-based learning was one method teachers might employ to help students learn English. The student’s English abilities and creativity could be enhanced while developing the project.